The Implementation of Differentiated Learning in English Teaching in Junior High Schools - Hermaniar, Yulieda; Fahmi Mubaraq, Yasyir; Winindyasari Palupi, Tri; Rusdiana, Ida (Intensive Journal, 2025)
The implementation of Kurikulum Merdeka in Indonesia emphasizes flexibility and essential learning materials to develop students' competencies and characters. Therefore, since 2022, all teachers are required to adapt student-centered learning methods in their teaching process. One of the proposed methods is differentiated learning that allows students to be recognized based on their learning preparation, learning interests and learning profiles. As regulation, teachers are required to create student profiles using various instruments to map students and become the basis of differentiated learning. When differentiated learning is implemented in Indonesia with various backgrounds both cultural and learning styles, teachers face new challenges. Therefore, this study was conducted to review the application of differentiated learning methods as part of the implementation of Kurikulum Merdeka. Observation is carried out by filling out an Observation Form that focuses on the application of differentiated learning based on the accuracy of content, process, and product. Interviews were also used to clarify the findings. Qualitative data obtained through the two methods were analyzed descriptively by following the stages proposed by Cresswell, namely transcribing, coding and classifying, interpreting, and drawing conclusions. The results showed the implementation of differentiated learning in public secondary schools in Tapin Regency. The implementation of differentiated learning is at the pre-learning stage, during learning, and at the evaluation stage.